Prognostic and clinical impact of PIK3CA mutation in gastric cancer: pyrosequencing technology and literature review. Issue 1 (December 2016) - Harada, Kazuto; Baba, Yoshifumi; Shigaki, Hironobu; Ishimoto, Takatsugu; Miyake, Keisuke; Kosumi, Keisuke; Tokunaga, Ryuma; Izumi, Daisuke; Ohuchi, Mayuko; Nakamura, Kenichi; Kiyozumi, Yuki; Kurashige, Junji; et al.
Abstract Background Phosphatidylinositol-4, 5-bisphosphate 3-kinase, catalytic subunit alpha (PIK3CA) mutations that activate the PI3K/AKT signaling pathway have been observed in several types of carcinoma and have been associated with patient prognosis. However, the significance of PIK3CA mutations in gastric cancer remains unclear. This retrospective study investigated the relationship between PIK3CA mutations and clinical outcomes in patients with gastric cancer. Additionally, we reviewed the rate of PIK3CA mutations in gastric cancer and the association between PIK3CA mutations and prognosis in human cancers. Methods The study included 208 patients with gastric cancer who underwent surgical resection at Kumamoto University Hospital, Japan, between January 2001 and August 2010. Mutations in PIK3CA exons 9 and 20 were quantified by pyrosequencing assays. Results PIK3CA mutations were detected in 25 (12 %) of the 208 patients. Ten patients had c.1634A > G (p.E545G), 10 had c.1624G > A (p.E542K), 13 had c.1633G > A (p.E545K), nine had c.3139C > T (p.H1047R), and 1 had c.3140A > G (p.H1047Y) mutations. PIK3CA mutations were not significantly associated with any clinical, epidemiologic, or pathologic characteristic. Kaplan–Meier analysis showed no significant differences in disease-free survival (log rankP  = 0.84) and overall survival (log rankP  = 0.74) between patients with and without PIK3CA mutations. Conclusions Mutations in PIK3CA did not correlate with prognosis in patients with gastric cancer, providing additional evidence for the lack of relationship between the two.